(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Natural or artificial collection of water serves as an optimum habitat that supports mosquito’s breeding, while savannah, grasslands or shady low woodlands supports their resting activities, swarming and mating. Samples were collected from breeding sites within some selected locations from January to June. Five hundred and thirty two mosquito larvae belonging to 3 genera Culex, Anopheles and Aedes were collected and seven species of mosquitoes were identified comprising; Culex quinquefasciatus 102 (19.17%), Aedes aegypti 345(64.84%), Culex decens 8 (1.50%), Aedes vittatus 49 (9.21%) Culex simpsoni 8(1.50%), Culex tigripes 17 (3.20%) and Anopheles gambiae 3(0.50%). Aedes aegypti was common in all the locations. Water samples were collected from seven different major breeding sites such as abandoned tyres 155(50.82%), Concrete gutters 50(16.39%), Pools 10 (3.27%) ponds 4 (1.31%), Plastic containers50 (16.39%), Potholes 6 (1.97%) and Metallic containers30 (9.84%) totaling 305 sampled breeding sites. The characteristics of breeding sites noted were the movement of water in the breeding places, the consistency of the presence of water in the breeding places, the existence of vegetation on the breeding and types of predators. Correlation analysis showed abundance of mosquitoes decreased with increase in physicochemical parameters. In conclusion, the common house mosquito (Aedes aegypti) was most abundant and occurring in abandoned tyres; while the physico-chemical parameters were all within the acceptable limits for mosquito breeding.